2016
DOI: 10.1002/cctc.201600120
|View full text |Cite
|
Sign up to set email alerts
|

Pillared Sn‐MWW Prepared by a Solid‐State‐Exchange Method and its Use as a Lewis Acid Catalyst

Abstract: Pillared Sn‐MWW (Sn‐MWW(SP)‐SSE) was prepared through a solid‐state‐exchange (SSE) route. The pillared structure was inherited from pillared B‐MWW, and Sn was inserted in the framework by boron leaching and solid‐state‐exchange with tin tetrachloride pentahydrate. The Sn‐MWW(SP)‐SSE with framework Sn sites exhibits Lewis acidity and good catalytic performance for the Baeyer–Villiger oxidation, and mono‐ and disaccharide isomerizations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 58 publications
(29 reference statements)
0
49
0
Order By: Relevance
“…The ability to tune their composition also provides opportunities in heterogeneous catalysis, especially when bifunctional catalysts are desirable, such as in the catalysis of tandem reactions . One such reaction is the isomerization of glucose to fructose in the presence of alcohols . First proposed by Saravanamurugan et al., it has been shown to be a high‐yield route to fructose and a promising alternative to aqueous routes.…”
Section: Methodsmentioning
confidence: 99%
“…The ability to tune their composition also provides opportunities in heterogeneous catalysis, especially when bifunctional catalysts are desirable, such as in the catalysis of tandem reactions . One such reaction is the isomerization of glucose to fructose in the presence of alcohols . First proposed by Saravanamurugan et al., it has been shown to be a high‐yield route to fructose and a promising alternative to aqueous routes.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, they enable beneficial effects on adsorption and reaction in processing bulky molecules. There are many reports about enhanced performance that can be achieved in catalysis when using 2D zeolite materials, especially for delaminated and pillared zeolite materials [36][37][38][39][40][41][42]. Overviews of 2D zeolites in catalysis have been published by J.Čejka [6,9,43] and J.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] One such reaction is the isomerization of glucose to fructose in the presence of alcohols. [27][28][29][30] First proposed by Saravanamurugan et al, [27] it has been shown to be ah igh-yield route to fructose and apromising alternative to aqueous routes.F or instance,when glucose isomerization to fructose is combined with fructose ketalization, increased fructose yields beyond the equilibrium levels are achievable and the obtained fructoside is readily hydrolyzed to fructose upon addition of water (Scheme 1).…”
mentioning
confidence: 99%